Re-examining Institutionalized Schooling: A New Era in Basic Education Institutions in Kenya - Caleb Mackatiani; Navin Mackatiani; Mercy Imbova (Profesi Pendidikan Dasar, 2022)
This study examined critical concerns for reconsidering the future of education in Kenya. These are power/authority, school processes and policies, and the curriculum. Schools have developed regulations that have evolved into school cultures, leading to the institutionalization of education. Learners are enslaved due to administrators' expectations based on institutionalization-causing factors. This study aimed to analyze the elements that influence institutionalized education in Kenya. The issue was examined using both qualitative and quantitative methodologies. The study utilized a 384-person sample with a confidence interval of 0.05, a confidence level of 95%, a Z-score of 1.96, and a standard deviation of 0.5. The study indicated that school policies influence the power and authority of institutionalized education. The study discovered that headship authority and power institutionalize schools. Power, policies, and curricula institutionalize the elementary and secondary levels of education. This has spurred disobedience among teachers and students.